INVESTIGATIVE ANALYSIS OF CURRICULUM IMPLEMENTATION (TEACHING/LECTURING) IN OBAFEMI AWOLOWO UNIVERSITY, ILE-IFE - Salami, Marie Onovroghene; Ojediran, Isaac Ayo (Advances in Social Sciences Research Journal, 2017)
The study investigated the type of environment under which the students of Obafemi Awolowo University (OAU), Ile-Ife, Nigeria, receive lectures, found out the student/teacher ratio of some of the classes and analysed the teaching style of some of the lecturers and the frequency with which lecturers attend their lectures. The results showed that many of the venues in which Part One courses are taken by students across Faculties like Mathematics, English and Chemistry and other courses that are Special electives, are overcrowded. The number of lecture venues is not increasing in proportion to annual increase in the admission of students into OAU. It also found out that lecturers find it difficult to put in their best during lectures as the number of students in some of the lecture theatres is so large that there is the need for the use of a public address system which may not be available. The study concluded that the conditions, including environment, for teaching and learning in OAU could become better if teaching and learning facilities are adequately provided.